Addressing Global Ruminant Agricultural Challenges Through Understanding the Rumen Microbiome: Past, Present, and Future - Huws, Sharon A.; Creevey, Christopher J.; Oyama, Linda B.; Mizrahi, Itzhak; Denman, Stuart E.; Popova, Milka; Muñoz-Tamayo, Rafael; Forano, Evelyne; Waters, Sinead M.; Hess, Matthias; Tapio, Ilma; Smidt, Hauke; et al. (Frontiers in Microbiology, 2018)
The rumen is a complex ecosystem composed of anaerobic bacteria, protozoa, fungi, methanogenic archaea and phages. These microbes interact closely to breakdown plant material that is inedible for humans, whilst providing metabolic energy to the host and producing methane. Consequently, ruminants produce meat and milk, which are rich in high quality protein, vitamins and minerals and therefore contribute to food security. As world population is predicted to reach approximately 9.7 billion by 2050, ruminant production has to increase to satisfy global protein demand, despite limited land availability, whilst ensuring environmental impact is minimised. These goals can be met by deepening our understanding of the rumen microbiome. Attempts to manipulate the rumen microbiome to benefit global agricultural challenges have been ongoing for decades with limited success, mostly due to the lack of a detailed understanding of this microbiome and our limited ability to culture most of these microbes outside the rumen. The potential to manipulate the rumen microbiome and meet global livestock challenges through animal breeding and introduction of dietary interventions during early life have recently emerged as promising new technologies. Our inability to phenotype ruminants in a high-throughput manner has also hampered progress, although the recent increase in ‘omic’ data may allow further development of mathematical models and rumen microbial gene biomarkers as proxies. Advances in computational tools, high-throughput sequencing technologies and cultivation-independent ‘omics’ approaches continue to revolutionise our understanding of the rumen microbiome. This will ultimately provide the knowledge framework needed to solve current and future ruminant livestock challenges.